CULTURAL AND LINGUISTIC-CULTURAL ASPECTS OF THE TEXTS IN PRIMARY SCHOOL TEXTBOOKS AND WORKBOOKS FOR THE RUSSIAN LANGUAGE - Слободанка Ж. Марковић (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2014)
<!-- p { margin-bottom: 0.1in; line-height: 120%; } --> This paper analyzes relevant textual materials with cultural content in current primary school textbooks for the Russian language. At fi rst we identifi ed linguistic-cultural texts (LCT) in all the analyzed textbooks and determined the relation between culturally neutral and culturally relevant texts. Next, we considered the issue of a foreign country's share, the share of the students' country, the content representing culture in contact, the culture of a third country and appendices with international values. Following this, we directed our attention to exact indicators of readability, thus determining the linguistic signifi cance of LCTs, and then moved onto testing the qualitative features of the presentation of cultural and linguistic-cultural facts, with a reference to the character of texts in accordance with the theme and the genre, a method by which culturally marked information is expressed with respect to the origin of the text and the subject of the announcement. We conclude that the author uses a modern approach; the textbooks strive to approach cultural values of Russia with credibility. They are rich in linguistic and cultural materials and different topics. For the fi rst time LCTs with religious themes are present, which is signifi cant for Serbian and Russian spiritual and orthodox connections and it points to a dialogue of the two cultures. The presumption that we started with is confi rmed: with age and an increase in the communicative competence, the number of texts related to the cultural information also grows - most of them are in the textbooks for the 7 th and the 8 th grade, while the least number is present in the textbooks for lower grades. All text types that are found in the general textbook theory are observed. Key words: textbook, text, culture, linguistic-cultural, transmission of culture, sociocultural competence.